The Role of the cooperation of tourist actors in cluster form in the attractiveness of territories: A qualitative study of Tangier city - OUBAIH, Younes; BENBBA, Brahim (International Journal of Scientific Research and Management (IJSRM), 2019)
In this paper we seek to study the nature of the relationship between tourism cooperation in the form of a cluster and the tourist attractiveness of their territories through, first, the presentation of a literature review that deals with the different facets of this issue and, secondly, through a qualitative exploratory study of tourism actors in the city of Tangier in order to assess the actors’ perception on the role that cluster-based networking could play in the development of the tourist attractiveness of Tangier city.